PERANCANGAN SISTEM INFORMASI PENGELOLAAN LAPANGAN FUTSAL DAN BADMINTON BERBASIS WEB (Studi Kasus: Leo Sport) - Prionggo Hendradi; Muhammad Ihsan Fathudin (FAKULTAS TEKNIK, 2024)
The development of internet-based technology, especially websites, is currently increasingly rapid and rapid. Currently, website-based technology allows business people to optimize this technology. Regarding this technology, this research aims to help improve and develop a more efficient system in order to obtain a marketing strategy in the form of a business brand and maximize services with the aim of facilitating performance in processing data, changing data, viewing information on futsal and badminton court schedules, including storing data online. automatically safe too. In designing this website, researchers used the waterfall method which consists of several steps, namely planning, analysis, design, implementation, testing and maintenance which were applied in developing the online field rental information system at Leo Sport. The data collection method uses interview techniques, observation, literature study, and uses the pieces method whose description consists of Performance, Information, Economy, Control, Efficiency, Service. This research produces a web-based information system that is able to manage field reservations, schedule settings, payments and reporting more efficiently, and helps business people increase futsal and badminton court rentals. Apart from that, so that the field rental business can increase, this system is facilitated with a payment model via the Midtrans gateway.